Klasyfikacja obiektów Międzynarodowej Drogi Wodnej E70 dla potrzeb analizy środowiskowej = The division of investment objects of the international waterway E70 for needs of environmental analysis - Hudak, Magda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The strengthening of economic development by complex progress of inland navigation system and the water tourism of four provinces: the Lubuskie, the Wielkopolska, the Kujawy-Pomerania and Pomeranian, with its sustainability development principle is the basic aim of "The conception of spatial inland waterway east-west: Oder, Warta River, Notec River, Bydgoszcz Canal, Brda River, Vistula, Nogat River, Szkarpawa River and the Vistula Bay revitalization (the planned in Poland International Waterway E70)".
Keywords: droga wodna; żegluga śródlądowa; Natura 2000; obszary chronione; waterway; inland waterway; areas of conservation